2023
DOI: 10.1186/s13048-023-01113-5
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in gonadotropin, apoptotic and metabolic pathways in granulosa cells warrant superior fertility of the Dummerstorf high fertility mouse line 1

Abstract: The development and maturation of ovarian follicles is a complex and highly regulated process, which is essential for successful ovulation. During recent decades, several mouse models provided insights into the regulation of folliculogenesis. In contrast to the commonly used transgenic or knockout mouse models, the Dummerstorf high-fertility mouse line 1 (FL1) is a worldwide unique selection experiment for increased female reproductive performance and extraordinary high fertility. Interactions of cycle-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…This process was achieved by competitively inhibiting the combination of IGF and IGFR (Insulin Like Growth Factor 1 Receptor) [ 49 ]. The IGF system has been widely documented to affect animal reproduction [ 50 , 51 ]. In vitro experiments at the pituitary level showed that exogenous IGF-1 can increase the secretion of LH in sheep pituitary cells [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…This process was achieved by competitively inhibiting the combination of IGF and IGFR (Insulin Like Growth Factor 1 Receptor) [ 49 ]. The IGF system has been widely documented to affect animal reproduction [ 50 , 51 ]. In vitro experiments at the pituitary level showed that exogenous IGF-1 can increase the secretion of LH in sheep pituitary cells [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis of granulosa cells is closely associated with follicular atresia ( Wang et al, 2023 ), process controlled by reproductive hormones and cytokines ( Santos et al, 2022 ; Bevilaqua et al, 2023 ; Grynberg et al, 2023 ; Li et al, 2023 ). Numerous studies performed in chicken, rodents and pigs have shown that proapoptotic and antiapoptotic factors contribute to follicular atresia triggering the apoptosis of granulosa cells ( Guo et al, 2019 ; Han et al, 2023 ; Ludwig et al, 2023 ). In the current study, we aimed, with the use of sRNA sequencing, to examine the effect of natural polyphenol RSV on apoptosis of porcine granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of SGK1 is present in oocytes of primordial follicles, and is very low or even undetected in granulosa cells of preantral follicles where the cells are proliferating at an extremely slow rate [ 37 ]. As the granulosa cells differentiate to nondividing luteal cells, SGK1 in immature granulosa cells is induced rapidly by FSH and more specifically LH, physiological stimulators of granulosa cell proliferation and differentiation [ 35 , 38 ]. Mediated by Sp1 binding region in the promotor of SGK1 gene, this marked increase of SGK1 expressions by FSH through the cAMP/PKA pathway is followed by a transient decline, and then reaches the maximal level as cells differentiate, coinciding temporally with the secondary burst of proliferative activity that occurs in granulosa cells of large preantral follicles as they come into preovulatory follicles [ 38 , 39 ].…”
Section: Sgk1 Involvement In Gametogenesismentioning
confidence: 99%
“…During follicular development, the induction of SGK1 is closely related to the specific stage of granulosa cell proliferation [ 36 ]. BMP15 and GDF9 promote FSH-induced progesterone synthesis in preovulatory follicular granulosa cells [ 72 ], and significantly increase the expression of SGK1 under the mediation of Sp1 [ 38 , 73 ]. Thus, BMP2, BMP7, BMP15 and GDF9 play a role in the regulation of SGK1.…”
Section: Sgk1 Involvement In Embryonic Developmentmentioning
confidence: 99%